Policing football ‘risk’?: a participant action research case study of a liaison-based approach to ‘public order’ - Stott, Clifford (Policing and society, 2018)
This paper reports upon the first formal academic analysis of the deployment of a dialogue based and explicitly non-coercive ‘Police Liaison Team’ (PLT) within the public order policing operation surrounding a football fixture. The study uses an approach based upon Participant Action Research to first generate changes to operational practices and then to analyse the consequences of these changes upon the dynamics of the event and of the public order policing operation itself. Data is drawn from multiple sources including direct observation and post event focus groups. It is argued that the PLT played an important role in terms of enhancing police capacity for dialogue and communication with ‘risk’ fans, adding depth and quality to risk assessment as well as assisting in the avoidance of ‘disorder’ and police coercion. Problems were identified in terms of strategy, inappropriate deployment of the resource by police commanders and resistance to change among police staff. The implication of the study for understanding ‘risk’ is discussed along with the role of PLTs in helping to achieve proportionality and efficiency in the policing of football.